Corrosion protection of steel cut‐edges by hot‐dip galvanized Al(Zn, Mg) coatings in 1 wt% NaCl: Part II. Numerical simulations. Issue 5 (2nd January 2019) - Dolgikh, Olga; Simillion, Hans; Lamaka, Sviatlana V.; Bastos, Alexandre C.; Xue, Huibin B.; Taryba, Maryna G.; Oliveira, Andre R.; Allély, Christian; Van Den Bossche, Bart; Van Den Bergh, Krista; De Strycker, Joost; Deconinck, Johan
Abstract : In this paper a mechanistic model is elaborated to simulate the corrosion behavior of aluminum–zinc–magnesium coatings on steel. The model is based on the mass transport and reactions of the ions in the electrolyte (MITReM). The finite element method has been used, which allows to perform time‐dependent simulations with micrometer scale to study local corrosion effects. The formation of corrosion products and the prediction of electrolyte concentration distributions are compared for different metallic coating compositions. The spatial and temporal simulation of complex precipitates provides an additional tool to validate the model through corrosion product characterization. The simulation results are compared to experimental observations, presented in part I of this paper. The MITReM simulations are limited to the micro‐scale and therefore to small geometries. A link is made with the potential model which can be applied on macro‐scale objects. A qualitative agreement is found between the simulations at both scales and the experiments. Further quantification of this model would optimize the simulations for material design and for predictive maintenance. Abstract : A mechanistic model for cut‐edge corrosion is developed and validated. The numerical experiments complement the experimental work (presented in part I of this work) and predict pH distribution, corrosion currents, ion distributions, and the precipitation of corrosion products. Both time dependent and spatially resolved results confirm the limited protection of the substrate by the formed corrosion products.